Aerobic denitrifying bacterial communities drive nitrate removal: Performance, metabolic activity, dynamics and interactions of core species. (November 2020) - Li, Sulin; Zhang, Haihan; Huang, Tinglin; Ma, Ben; Miao, Yutian; Shi, Yinjie; Xu, Lei; Liu, Kaiwen; Huang, Xin
Graphical abstract: Highlights: Three novel Mix-CADB consortia were obtained. The TOC and nitrate removal efficiencies were greater than 93% and 98%. Mix-CADB consortia exhibited higher carbon metabolic activity. Co-existence of Mix-CADB core species drove nutrient removal. Highest predicted TN removal efficiency reached 99% by D14 community. Abstract: Three novel mix-cultured aerobic denitrifying bacteria (Mix-CADB) consortia named D14, X21, and CL exhibited excellent total organic carbon (TOC) removal and aerobic denitrification capacities. The TOC and nitrate removal efficiencies were higher than 93.00% and 98.00%. The results of Biolog demonstrated that three communities displayed high carbon metabolic activity. nirS gene sequencing and ecological network model revealed that Pseudomonas stutzeri, Paracoccus sp., and Paracoccus denitrificans dominated in the D14, X21, and CL communities. The dynamics and co-existence of core species in communities drove the nutrient removal. Response surface methodology showed the predicted total nitrogen removal efficiency reached 99.43% for D14 community. The three Mix-CADB consortia have great potential for nitrogen-polluted aquatic water treatment because of their strong adaptability and removal performance. These results will provide new understanding of co-existence, interaction and dynamics of Mix-CADB consortia for nitrogen removal in nitrogen-polluted aquatic ecosystems.